2015
DOI: 10.7314/apjcp.2015.16.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Association between the DICER rs1057035 Polymorphism and Cancer Risk: Evidence from a Meta-analysis of 1,2675 Individuals

Abstract: Background: DICER, one of the microRNA (miRNA) biogenesis proteins, is involved in the maturation of miRNAs and is implicated in cancer development and progression. The results from previous epidemiological studies on associations between DICER rs1057035 polymorphism and cancer risk were inconsistent. Thereforewe performed this meta-analysis to summarize possible associations. Materials and Methods: We searched all relevant articles on associations between DICER rs1057035 polymorphism and cancer risk from PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…However, conclusions of miRNA biogenesis pathway genes polymorphisms and cancer risk remain inconsistent, which may cause by the heterogeneity of the cancer subtype, sample size and the ethnicity of patients. Yu, Kuang & Yin (2015) conducted a meta-analysis synthesizes sevens studies with multi-type cancer and found the C allele of the DICER rs1057035 polymorphism probably decreases cancer risk (We included more studies in our studies and found the same results in DICER rs1057035). This study based on the association of a single SNP or gene with cancer risk, which may weaken gene’s biological value.…”
Section: Discussionmentioning
confidence: 93%
“…However, conclusions of miRNA biogenesis pathway genes polymorphisms and cancer risk remain inconsistent, which may cause by the heterogeneity of the cancer subtype, sample size and the ethnicity of patients. Yu, Kuang & Yin (2015) conducted a meta-analysis synthesizes sevens studies with multi-type cancer and found the C allele of the DICER rs1057035 polymorphism probably decreases cancer risk (We included more studies in our studies and found the same results in DICER rs1057035). This study based on the association of a single SNP or gene with cancer risk, which may weaken gene’s biological value.…”
Section: Discussionmentioning
confidence: 93%
“…For example, some studies found association between Dicer1 rs3742330 and rs1057035 polymorphisms, and various cancer susceptibility and/or survival in cancerous patients with T cell lymphoma and hepatocellular carcinoma. 16,34 In a meta-analysis, Yu et al 35 The effect of Dicer1 rs3742330/Drosha rs10719GG/TC +CC, Dicer1 rs3742330/RAN rs14035 GG/CC, and Dicer1 rs3742330/XPO5 rs11077 GG/AC+CC combinations with the increased risk of idiopathic recurrent pregnancy loss has been shown by Jung et al 22 Moreover, they showed the association between RAN rs14035 CT, Dicer1 rs3742330/ RAN rs14035 AA+AG/CT+TT, Drosha rs10719/RAN rs14035 TC+CC/CT+TT, and RAN rs14035/XPO5 rs11077 CT+TT/AA combinations and the reduced risk of this complication. The relationship between Dicer1 rs3742330 A allele and AA genotype with azoospermia was reported by Fu et al 38 The TT genotype of the Dicer1 rs1057035 polymorphism was associated with the lower risk of Graves' disease development (P = 0.0098).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found the relationship between DICER1 and DROSHA polymorphisms and several diseases, but the published reports on their impacts on RSA are rare …”
Section: Discussionmentioning
confidence: 99%
“…DROSHA and DICER1 genes are located on chromosomes 5 and 14, respectively . There are several single nucleotide polymorphisms (SNPs) in DROSHA and DICER1 genes, and their effects on various diseases have been investigated …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation